Electoral institutions, cabinet negotiations, and budget deficits in the European Union - Hallerberg, Mark 1967-; Hagen, Jürgen von 1955- (1997)
A rough consensus has emerged that states with proportional representation systems are likely to run larger deficits than plurality states. We argue that electoral institutions matter because they restrict the type of budgetary institution at the governmental phase which a state has at its disposal. Cabinet members may willingly delegate authority to a finance minister who can monitor spending ministers and punish those who defect in a process we label delegation procedure is feasible in states where one-party governments are the norm. Such states usually have plurality electoral systems. In multi-party governments, which are common in states with proportional representation, the coalition members are not willing to delegate to one actor the ability to monitor and punish the others. Negotiated targets in the form of fiscal contracts provide an alternative in multi-party governments. Pooled time series regression results for the current European Union states in the period 1981-94 support our contention that it is the presence or absence of one of these budgetary institutions, rather than the plurality/proportional representation" dichotomy, which has the greatest impact on debt levels.
Keywords: Ökonometrisches Modell; Budget deficits -- European Union countries -- Econometric models; Cabinet officers -- European Union countries -- Econometric models; Elections -- European Union countries -- Econometric models; Europäische Union. Mitgliedsstaaten